(untitled) (Research, Society and Development, 2022)
The extraction of third molars are common procedures in dental practice. However, during the surgical procedure for its removal, postoperative consequences can be observed. Therefore, piezosurgery, which uses ultrasonic waves to perform the removal of these dental elements, has been studied to find a technique capable of reducing these consequences, such as edema, pain and trauma in nerve structures. Hence, the objective of this work is to conduct an integrative review of the literature, in order to evidence the applicability of piezosurgery in the extraction of third molars, evaluating its advantages and its limitations. For this reason, a research was performed in the PubMed, BVS and Cochrane Library databases. The inclusion criteria corresponded to the free and complete availability of the articles, which were related to the theme, with a 10-year time lapse. The duplicate studies, theses, monographs and studies associating piezosurgery with another material/substance, which did not have Portuguese language based or English and Spanish translations, were not included. After the application of the criteria, 14 articles were left to form the study, in which it was noticed that the use of piezosurgery in the extraction of third molars results in a decrease in postoperative problems that may exist.